2008
DOI: 10.1002/prca.200780112
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal cytoskeletal protein expression in cultured skin fibroblasts from type 1 diabetes mellitus patients with nephropathy: A proteomic approach

Abstract: Diabetic nephropathy (DN) develops in about 40% of insulin-dependent type 1 diabetes mellitus (T1DM) patients, and is associated not only with diabetes duration and metabolic control, but also with a genetic predisposition. Constitutive alterations of cytoskeletal proteins may play a role in the development of DN. We investigated the expression of these proteins in cultured skin fibroblasts, obtained from long-term T1DM patients with and without DN but comparable metabolic control, and from matched healthy sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 54 publications
2
14
0
Order By: Relevance
“…We found only one study (a casecontrol one), performed by Conway et al, examining the association of polymorphism of this candidate gene with diabetic nephropathy development in type 1 diabetes, and our family-based association study confirms their findings [17]. Evidence also exists that there are some proteins differentially expressed in cultured fibroblast in patients with type 1 diabetes with established nephropathy, compared to the ones without that complication and, typically, altered protein classes consist of the actin-associated protein, including caldesmon [21]. This information is consistent with the results of in vivo and in vitro studies pointing out the importance of genes that regulate the actin filament organisation in diabetic nephropathy development.…”
Section: Discussionsupporting
confidence: 85%
“…We found only one study (a casecontrol one), performed by Conway et al, examining the association of polymorphism of this candidate gene with diabetic nephropathy development in type 1 diabetes, and our family-based association study confirms their findings [17]. Evidence also exists that there are some proteins differentially expressed in cultured fibroblast in patients with type 1 diabetes with established nephropathy, compared to the ones without that complication and, typically, altered protein classes consist of the actin-associated protein, including caldesmon [21]. This information is consistent with the results of in vivo and in vitro studies pointing out the importance of genes that regulate the actin filament organisation in diabetic nephropathy development.…”
Section: Discussionsupporting
confidence: 85%
“…In this way, we obtained an estimated permutation-based FDR [18] at 3.64%, still less than the FDR control level of 5%. In fact, several studies published later than the WTCCC paper [17] also supported the association of these three genes with T1D ( INS [19][22], CALD1 [23], [24], and PD-1 [25], [26]). …”
Section: Resultsmentioning
confidence: 84%
“…Protein identification was performed by matrix‐assisted laser desorption/ionization mass spectrometry. We showed that several proteins are differentially expressed between cultured skin fibroblasts from T1DM patients with and without established diabetic nephropathy 55–57, evidencing an association between diabetic nephropathy and the constitutive expression of some proteins, thus suggesting their involvement in the development of diabetic nephropathy. We showed alterations in the abundance of nine molecular chaperones controlling protein turnover and folding in cultured skin fibroblasts from T1DM patients with diabetic nephropathy 57.…”
Section: Fibroblast Proteome Profilingmentioning
confidence: 81%
“…Recently, we performed a comparative proteomic analysis of cultured skin fibroblasts from T1DM patients with and without diabetic nephropathy and from healthy controls 15, 55–58. Proteins were separated by two‐dimensional electrophoresis and the gel images were qualitatively and quantitatively analysed.…”
Section: Fibroblast Proteome Profilingmentioning
confidence: 99%
See 1 more Smart Citation